(3JcfhdhLjG GdeYdheGJ aj efXeGJ GdGYeGd (B:s (3GdGSJNOGeGJ h GdJWHjbGJ (B/s - (3GddGej, ZSGf bGSe OGhOs; (3TcQhdj GdHjGJj, CejQI s ((3YeGf(B: s (3eDSSI GdhQGb(B, s, 2009)
(3JWHjbGJ JcfhdhLjG GdeYdheGJ aj eLGdGdJ GdGfJGL , GdGfXeI GdNHjQI h GdPcGA GdUfGYj GdTHcI GdYUHhfjI GdUfGYjI , THcGJ GdGJUGd , GdGYeGd GdGdcJQhfjI h GdJLGQI GdGdcJQhfjI , EOGQI GdeYQaI , Cef THcI GdeYdheGJ h eYGdLJg(B.s
(3eQGLY (B: (3dcd aUd eQLYs
Keywords: (3EOGQI GdGYeGds; (3JcfhdhLjG GdeYdheGJs; (3efXeGJ CUMGH GdYeds